2000
DOI: 10.1002/1521-1878(200011)22:11<997::aid-bies6>3.0.co;2-#
|View full text |Cite
|
Sign up to set email alerts
|

The puzzle of PCNA's many partners

Abstract: The identification of proteins that interact with proliferating cell nuclear antigen (PCNA) has recently been a rapidly expanding field of discovery. PCNA is involved in many aspects of DNA replication and processing, forming a sliding platform that can mediate the interaction of proteins with DNA. It is striking that many proteins bind to PCNA through a small region containing a conserved motif; these include proteins involved in cell cycle regulation as well as those involved in DNA processing. Sequential an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
279
0
1

Year Published

2003
2003
2017
2017

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 409 publications
(284 citation statements)
references
References 90 publications
4
279
0
1
Order By: Relevance
“…A similar observation regarding the p21-PCNA interaction was reported by Flores-Rozas et al [48], who found that on average 2.3 molecules of p21/Cipl (monomer) bound to 1 molecule of PCNA trimer. The N-terminus of UNG2 shares the PCNA consensus binding motif with several proteins involved in DNA replication and repair, including MSH3, MSH6, FEN1, MCMT, and LIG1 [44]. In light of these many interactions, it is attractive to envision a model in which UNG2 participates in a multi-protein complex associated with the replication fork in order to remove uracil residues that result from dUMP incorporation in place of dTMP opposite dAMP.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A similar observation regarding the p21-PCNA interaction was reported by Flores-Rozas et al [48], who found that on average 2.3 molecules of p21/Cipl (monomer) bound to 1 molecule of PCNA trimer. The N-terminus of UNG2 shares the PCNA consensus binding motif with several proteins involved in DNA replication and repair, including MSH3, MSH6, FEN1, MCMT, and LIG1 [44]. In light of these many interactions, it is attractive to envision a model in which UNG2 participates in a multi-protein complex associated with the replication fork in order to remove uracil residues that result from dUMP incorporation in place of dTMP opposite dAMP.…”
Section: Discussionmentioning
confidence: 99%
“…The extreme N-terminus of UNG2 bears a consensus PCNA-binding motif shared by p21, MSH6, LIG1, XPG, FEN1, and many other proteins involved in DNA transactions [44]. In a seminal crystal structure of PCNA, a p21 peptide encompassing the binding motif was shown to bind to the interdomain connector loop (IDCL) region of PCNA [25].…”
Section: Influence Of Mutations In the Interdomain Connector Loop Of mentioning
confidence: 99%
“…A PCNA ring may bind to different protein partners at different time and space to carry out specific tasks [3,5,16,17]. We previously found that the level of PCNA is substantially elevated in cancer cells, which is only notable difference between cancer and normal cells with respect to PCNA protein [18].…”
Section: Introductionmentioning
confidence: 99%
“…27 The 300 amino acids at the Cterminal end of the protein, beyond the I region, are also engaged in protein-protein interactions; this region contains interaction sites with TFIIH and CSB and a PIP-box motif that mediates an interaction with PCNA. 24,28,29 A second interaction site with TFIIH is consistent with a strong functional interaction between XPG and TFIIH. 30 The functional significance of the interaction of XPG with CSB and PCNA has not yet been established.…”
Section: Discovery and Cloning Of Xpgsupporting
confidence: 54%